A comparison of oral artesunate and artemether antimalarial bioactivities in acute falciparum malaria. - Suputtamongkol, Y; Newton, P; Angus, B; Teja-Isavadharm, P; Keeratithakul, D; Rasameesoraj, M; Pukrittayakamee, S; White, N (2001)
AIMS: Artesunate and artemether are the two most widely used artemisinin derivatives in the treatment of uncomplicated Plasmodium falciparum malaria, but there is little information on their comparative pharmacokinetics. The aim of this study was to examine the relative oral antimalarial bioavailability and pharmacokinetics of the two derivatives. METHODS: The pharmacokinetic properties of oral artesunate and artemether (4 mg kg(-1)) were compared in a randomized cross-over study of 14 adult patients in western Thailand with acute uncomplicated Plasmodium falciparum malaria. Antimalarial activity was compared using a previously validated, sensitive bioassay. RESULTS: Despite a 29% lower molar dose, oral artesunate administration resulted in significantly larger mean area under the plasma antimalarial activity time curve and median maximum plasma antimalarial activity than after oral artemether (P